2018
DOI: 10.1159/000487288
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Immune Response to Tumor Burden Predicts Survival Via Regulating Functions of Lymphocytes and Monocytes in Diffuse Large B-Cell Lymphoma

Abstract: Background/Aims: Diffuse large B-cell lymphoma (DLBCL) is an aggressive disease, and is the most common type of lymphoma in adults. Although significant progress in treatment has been made using chemotherapy combinations, there exist a large amount of relapse or refractory cases. Thus, effective clinical biomarkers for DLBCL are urgently needed. Our study aims to explore the predictive significance of using the immune response to tumor burden ratio [defined as the lymphocyte to monocyte ratio (LMR)/lactate deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
(42 reference statements)
2
26
0
1
Order By: Relevance
“…Serum LDH was demonstrated by Ji et al [20] as a perfect surrogate marker of tumour burden in DLBCL patients. Therefore, the positive correlation between baseline fibrinogen and LDH levels in our study might suggest a possible connection between fibrinogen level and tumour burden.…”
Section: Discussionmentioning
confidence: 96%
“…Serum LDH was demonstrated by Ji et al [20] as a perfect surrogate marker of tumour burden in DLBCL patients. Therefore, the positive correlation between baseline fibrinogen and LDH levels in our study might suggest a possible connection between fibrinogen level and tumour burden.…”
Section: Discussionmentioning
confidence: 96%
“…To the best of our knowledge, this is the first study to estimate the prognostic value of the LMR in RT-treated patients with WR-B-NHL and investigate the potential application of the LMR combined with RT on the systemic immune response, as well as the combination of RT with immunotherapies. Accumulating studies have demonstrated that survival outcomes in patients with lymphoma are associated with systemic inflammation (22)(23)(24)(30)(31)(32). The peripheral inflammatory cells, including lymphocytes and monocytes, represent significant markers of systematic inflammatory response (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the LMR may be a better biomarker to evaluate the immune activities of the host. As reported, the LMR may reflect the degree of systemic immunity and is regarded as an important prognostic indicator in a variety of malignancies, including B-NHL (22)(23)(24). There are several studies focusing on the role of the LMR on therapeutic responsiveness of chemotherapy regimens (30,37); however, few studies have compared the LMR with clinical response to RT (38), which is also an important therapeutic modality to treat patients with WR-B-NHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Limfosit mempunyai efek anti-tumor yang penting dalam imunitas tubuh. 33 Dengan tingginya kadar limfosit, maka sistem imunitas tubuh semakin kuat sehingga risiko neutropenia pascakemoterapi akan lebih rendah. Aktivasi limfosit T merupakan langkah utama pada keadaan respons imun yang efektif.…”
Section: Diskusiunclassified